Exosomes enriched with miR-124-3p show therapeutic potential in a new microfluidic triculture model that recapitulates neuron–glia crosstalk in Alzheimer’s disease - Évora, Artemizia; Garcia, Gonçalo; Rubi, Ana; De Vitis, Eleonora; Matos, Ana Teresa; Vaz, Ana Rita; Gervaso, Francesca; Gigli, Giuseppe; Polini, Alessandro; Brites, Dora (Frontiers in Pharmacology, 2025)
BackgroundAlzheimer’s disease (AD), a complex neurodegenerative disease associated with ageing, is the leading cause of dementia. Few people with early AD are eligible for the novel Food and Drug Administration (FDA)-approved drug treatments. Accordingly, new tools and early diagnosis markers are required to predict subtypes, individual stages, and the most suitable personalized treatment. We previously demonstrated that the regulation of microRNA (miR)-124 is crucial for proper neuronal function and microglia reshaping in human AD cell models.ObjectiveThe aim of this study was to develop an efficient miR-124-3p-loaded exosome strategy and validate its therapeutic potential in using a multi-compartment microfluidic device of neuron–glia that recapitulates age-AD pathological features.Methods and resultsUsing cortical microglia from mouse pups, separated from glial mixed cultures and maintained for 2 days in vitro (stressed microglia), we tested the effects of SH-SY5Y-derived exosomes loaded with miR-124-3p mimic either by their direct transfection with Exo-Fect™ (ET124) or by their isolation from the secretome of miR-124 transfected cells (CT124). ET124 revealed better delivery effciency and higher potent effects in improving the stressed microglia status than CT124. Tricultures of human SH-SY5Y neuroblastoma cells (SH-WT) were established in the presence of the human microglia cell line (HMC3) and immortalized human astrocytes (IM-HA) in tricompartmentalized microfluidic devices. Replacement of SH-WT cells with those transfected with APP695 (SH-SWE) in the tricultures and addition of low doses of hydrogen peroxide were used to simulate late-onset AD. The system mimicked AD-associated neurodegeneration and neuroinflammation processes. Notably, ET124 exhibited neuroprotective properties across the three cell types in the AD model by preventing neuronal apoptosis and neurite deficits, redirecting microglial profiles towards a steady state, and attenuating the inflammatory and miRNA fingerprints associated with astrocyte reactivity.ConclusionTo the best of our knowledge, this is the first study supporting the neuro- and immunoprotective properties of miR-124-engineered exosomes in a microfluidic triculture platform, recapitulating age-related susceptibility to AD. Our system offers potential to develop personalized medicines in AD patient subtypes.